Oświetlające się plany. Ciche i dalekie w „Extremely Loud and Incredibly Close” Jonathana Safrana Foera - Joanna Roszak (Studia Litteraria et Historica, 2014)
Mutually illuminating planes: the silent and the distant in J.S. Foer’s 'Extremely Loud and Incredibly Close'